2020
DOI: 10.1039/d0cc06514e
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-enhanced direct conversion of CO2 to CO over oxygen-deficient Mo-doped CeO2

Abstract: Oxygen-deficient Mo-doped CeO2 showed significantly higher CO2 conversion compared to pure CeO2 in the plasma splitting of CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The XPS peaks at 531.1 eV corresponding absorbed oxygen is considered to represent oxygen vacancy V O . 23 Peak areas of V O and O L (lattice oxygen) are used to estimate the relative concentration of V O , 23 so the relative concentrations of V O are 23.88 and 41.72%, respectively, in 30% VT and DBD-30% VT samples, illustrating that Ar plasma treatment increased the content of oxygen vacancies by 74.71%. The increase in the oxygen vacancy content provides more active sites for CO 2 dissociation and reduces the recombination rate of charge carriers, resulting in the improvement of catalytic performance.…”
Section: Influence Of Dbd Plasma Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The XPS peaks at 531.1 eV corresponding absorbed oxygen is considered to represent oxygen vacancy V O . 23 Peak areas of V O and O L (lattice oxygen) are used to estimate the relative concentration of V O , 23 so the relative concentrations of V O are 23.88 and 41.72%, respectively, in 30% VT and DBD-30% VT samples, illustrating that Ar plasma treatment increased the content of oxygen vacancies by 74.71%. The increase in the oxygen vacancy content provides more active sites for CO 2 dissociation and reduces the recombination rate of charge carriers, resulting in the improvement of catalytic performance.…”
Section: Influence Of Dbd Plasma Pretreatmentmentioning
confidence: 99%
“…Wang et al found a 20 times higher CO 2 conversion rate compared to pure CeO 2 when filling oxygen-deficient Modoped CeO 2 in a DBD reactor because oxygen vacancies (V O ) as active sites promote CO 2 adsorption and dissociation. 23 Chen et al reported that Ar plasma-treated NiO/TiO 2 downstream of MW discharge increases almost by a factor of 2 the conversion rate and energy efficiency. 24 However, the dissociation of CO 2 comes from the direct excitation of CO 2 rather than the vibrational excitation in DBD resulting in limited energy efficiencies, and MW plasmas are not suitable in atmospheric environments.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 These sites can be coordinated by solvent molecules and are expected to contribute to photocatalytic activity as Lewis acid sites in organic photocatalysis. [33][34][35] Herein, we synthesized a two dimensional Dy(III) metalorganic layer (MOL 1) using Dy(NO 3 ) [1,2,5]thiadiazole-4,7-diyl)dibenzoic acid) under solvothermal conditions. The structural analysis of MOL 1 showed that the eight-fold coordinated Dy1 was surrounded by eight oxygen atoms from six L 2− ligands.…”
mentioning
confidence: 91%
“…1 With in-depth research, semiconductor materials, including ZnO, CeO 2 , CdS, g-C 3 N 4 , etc., have gradually gained attention in various branches of photocatalysis. [2][3][4][5][6][7][8][9][10] However, their wide and fixed band gap, the rapid recombination of photogenerated excitons and the slow surface catalytic kinetics have seriously hindered their further development. 11 Therefore, scientists have been committed to seeking new photocatalysts with high catalytic activity, selectivity and stability.…”
mentioning
confidence: 99%
“…The vibrationally excited CO 2 and H species were suggested to significantly enhance the key reaction pathway of decomposition of the formate intermediate to produce CO on the Pd 2 Ga/SiO 2 catalyst, and finally the thermodynamic equilibrium limitation was overcome. Wang et al 25 reported that plasma could promote the Mo-doped CeO 2 catalyst to achieve CO 2 decomposition to CO at room temperature and a synergy factor of 3 was attained. Though the reaction enhancement and synergistic effect of plasma catalysis for CO 2 hydrogenation have been extensively investigated, the design and establishment of a new reaction route has rarely been reported till date.…”
Section: Introductionmentioning
confidence: 99%